Enhanced resistive switching performance for bilayer HfO2/TiO2 resistive random access memory. (1st September 2016) - Ye, Cong; Deng, Tengfei; Zhang, Junchi; Shen, Liangping; He, Pin; Wei, Wei; Wang, Hao
Abstract: We prepared bilayer HfO2 /TiO2 resistive random accessory memory (RRAM) using magnetron sputtering on an ITO/PEN flexible substrate. The switching voltages ( V SET and V RESET ) were smaller for the Pt/HfO2 /TiO2 /ITO device than for a Pt/HfO2 /ITO memory device. The insertion of a TiO2 layer in the switching layer was inferred to act as an oxygen reservoir to reduce the switching voltages. In addition, greatly improved uniformity was achieved, which showed the coefficient of the variations of V SET and V RESET to be 9.90% and 6.35% for the bilayer structure RRAM. We deduced that occurrence of conductive filament connection/rupture at the interface of the HfO2 and TiO2, in combination with the HfO2 acting as a virtual cathode, led to the improved uniformity. A multilevel storage capability can be obtained by varying the stop voltage in the RESET process for bilayer HfO2 /TiO2 RRAM. By analyzing the current conduction mechanism, we demonstrated that the multilevel high resistance state (HRS) was attributable to the increased barrier height when the stop voltage was increased.